2013
DOI: 10.1039/c3nr00344b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced visible-light-driven photocatalytic activity of mesoporous TiO2−xNx derived from the ethylenediamine-based complex

Abstract: A facile solvent evaporation induced self-assembly (SEISA) strategy was developed to synthesize mesoporous N-doped anatase TiO 2 (SE-meso-TON) using a single organic complex precursor derived in situ from titanium butoxide and ethylenediamine in ethanol solution. After the evaporation of ethanol in a fume hood and subsequent calcinations at 450 C, the obtained N-doped TiO 2 (meso-TON)anatase was of finite crystallite size, developed porosity, large surface area (101 m 2 g À1) and extended light absorption in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 45 publications
5
35
0
1
Order By: Relevance
“…Our BET results show that the specific surface area increased from (101), (004) and (200) [10]. Other studies also reported the absence of Ti-N crystal peak in the XRD patterns for their N-doped TiO 2 particles [7,8,18,19].…”
Section: Synthesis and Characterisation Of The Ntk Catalystssupporting
confidence: 54%
“…Our BET results show that the specific surface area increased from (101), (004) and (200) [10]. Other studies also reported the absence of Ti-N crystal peak in the XRD patterns for their N-doped TiO 2 particles [7,8,18,19].…”
Section: Synthesis and Characterisation Of The Ntk Catalystssupporting
confidence: 54%
“…Despite the fact that suitable amount of O vac can extend light absorption into visible light region and improve photocatalytic activity, the photoreactivity will drop dramatically if O vac concentration is greater than certain amount. 15,23 In this research, the C-doping level is quite high with almost 4.3 at.% carbide-based C 4À coexisting with comparable amount of O vac in the C-doped ZnO. Hence, the low visible-light-driven photocatalytic activity on the C-doped ZnO was tentatively assigned to the synergistic consequences of the overloaded C-dopants and O vac that favour the recombination of photogenerated charge carriers under irradiation.…”
Section: Photocatalytic Activitymentioning
confidence: 87%
“…Besides bandgap light absorption, visible-light absorption on the C-doped ZnO is also tailed beyond 800 nm which is a typical red shi induced by impurity adsorption or oxygen-vacancies (O vac ). 15,23 Advanced characterisations are necessary to determine C-species and O vac for understanding the nature of visible-light response on the C-doped ZnO.…”
Section: 8mentioning
confidence: 99%
See 2 more Smart Citations